Investigating Serum and Placental Levels of IGF-1 and IGF-1R in Preeclampsia Patients and Their Clinical Implications - Su J; Huang X; Meng S; Wang S (International Journal of Women's Health)
Junyou Su,1,* Xiaoting Huang,1,* Shengping Meng,2 Sumei Wang2 1Department of Obstetrics, The Second Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, 530007, People’s Republic of China; 2Department of Obstetrics, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, 530021, People’s Republic of China*These authors contributed equally to this workCorrespondence: Sumei Wang, Email wangsumei0722@163.comObjective: To investigate the levels of insulin-like growth factor-1 (IGF-1) and insulin-like growth factor-1 receptor (IGF-1R) in the serum and placenta of patients with preeclampsia (PE), establish their correlations, and evaluate their diagnostic potential.Methods: 22 PE patients and 22 normal pregnant women who underwent cesarean section deliveries at the First Affiliated Hospital of Guangxi Medical University between December 2021 and December 2022 were included in the observation group and the control group. Enzyme-linked immunosorbent assay (ELISA) was utilized to measure the levels of IGF-1 and IGF-1R in serum samples, and immunohistochemical techniques (IHC) were employed to evaluate the levels of IGF-1 and IGF-1R in placental samples. The association between IGF-1, IGF-1R, and PE was analyzed, and the diagnostic accuracy of serum IGF-1 and IGF-1R for PE was assessed by ROC curve analysis.Results: The levels of IGF-1 and IGF-1R in the serum and average optical density (AOD) value of IGF-1 and IGF-1R in placental tissue of the observation group were significantly lower. In the group with PE, there was a reduction in the number of positive cells for IGF-1 and IGF-1R in placental tissue. Positive correlations were noted between IGF-1 and IGF-1R levels in both serum and placental tissue and neonatal birth weight. The ROC curve analysis revealed that serum IGF-1 exhibited an AUC of 0.944 for diagnosing PE, with a sensitivity of 86.00% and specificity of 100.00%. Serum IGF-1R showed an AUC of 0.820 for diagnosing PE, with a sensitivity of 77.00% and specificity of 77.00%.Conclusion: The expression of IGF-1 and IGF-1R in the serum and placental tissues of preeclamptic pregnant women was significantly reduced. This reduction implies that IGF-1 and IGF-1R may potentially be used as biomarkers in the clinical prediction, diagnosis, and prognosis evaluation of PE.Keywords: hypertensive disorders of pregnancy, preeclampsia, IGF-1, IGF-1R, pregnancy